A Study on Quality of Work Life Among Nurses in A Medical College Hospital in Bangalore - Ramesh, Naveen; Nisha, Catherine; Josephine, Andre Mary; Thomas, Seena; Joseph, Bobby (National Journal of Community Medicine, 2013)
Introduction: Quality of Work Life (QWL) is defined as the extent to which an employee is satisfied with personal and working needs through participating in the workplace while achieving the goals of the organization. Objectives: To assess the quality of life of nurses working in a medical college hospital in Bangalore and the factors associated with it. Methods: Ethical approval from the institution and informed consent from the study participants was obtained and quality of life questionnaire was administered to all the nurses working in the hospital. Results: A total of 671 (88.5%) nurses participated in the study. Among the participants, 452 (67.7%) indicated that they have the autonomy to make patient care decisions, 500 (74.9%) were unable to balance their work and family lives, 656 (98.2%) were stressed in their work and 543 (81.3%) of nurses were unable to complete their work in the time available. Conclusion: It is important to consider the quality of working life of the nurses to improve productivity and performance of the nurses.